Corporate governance impact on integrated reporting disclosure quality: evidence from preand post-COVID-19 on Chinese listed firms - Siyuan, Yang; Jalila, Johari (Human Resources Management Academic Research Society (HRMARS), 2024)
This study delves into the intricate relationship between corporate governance practices and integrated reporting disclosure. Focusing on 79 companies listed on the Shenzhen Stock Exchange, we scrutinize five pivotal variables: the top five shareholders’ shareholding percentage, independent directors’ representation, CEO duality, gender diversity within the board of directors, and the influence of institutional investors. Leveraging the Hausman test and a fixed-effects model, we draw on data sourced from the Choice Financial Terminal for governance metrics and firms annual report for integrated reporting information. To test these hypotheses, the study employs a regression model on a sample of Chinese listed firms, utilizing an integrated reporting quality scorecard to measure the extent and quality of their disclosures. Our findings reveal a nuanced landscape: while a negative correlation emerges between the shareholding percentage of top shareholders and integrated reporting quality from 2018 to 2019, other variables—including independent directors, CEO duality, gender diversity, and institutional investors—do not show significant impacts during this period. Interestingly, gender diversity displays a negative correlation in 2021-2022, contrasting with the neutral impact observed for the other variables. This study enriches our understanding of corporate governance mechanisms influencing disclosure practices, particularly within China's evolving economic landscape, pre- and post-COVID-19. By achieving these research objectives, this study aims to provide insights to the academic community on the relationship between corporate governance and disclosure and to provide recommendations to help firms better cope with future crises and improve the quality of disclosure. These endeavors are expected to provide solutions to the new challenges posed by the global health crisis in corporate business management.